Orientasi Masa Depan terkait Pernikahan pada Dewasa Lajang Asal Nusa Tenggara Timur yang Merantau di Jakarta - nepasiki, Lidia Silistiani; Arianti, Rudangta (Penerbit Goodwood, 2023)
Purpose: The aim of the study is to know the concept of future orientation about marriage in single adults from East Nusa Tenggara who live in Jakarta Barat, specifically in the age range of late thirties to approaching forty years old. Methodology/approach: This research uses 2 participants with criteria is an early adult male and female with an age range from late 30 to 40 years, already working, not living with parents, and not yet married in Jakarta. There were 2 participants in this research, namely: adult men (38 years) and adult women (37 years) who were unmarried and had migrated to Jakarta. The data collection method used by researchers is a semi-structured in-depth interview technique referring to the interview guide that has been prepared. Results/findings: The results indicated that the need to resolve a crisis of trust in a partner because one's own desires affect the future orientation related to marriage in the participants, and therefore caused them to remain unmarried. Conclusions: The study finds that single adults from East Nusa Tenggara in Jakarta delay marriage due to personal motivations, including trust issues and self-preference. Clear future orientation helps them plan, evaluate, and prepare for marriage despite existing challenges. Limitations: From the results of the research and discussion carried out, it can be concluded that the picture of future orientation regarding marriage in single adults from East Nusa Tenggara who migrated to West Jakarta is that the two participants have specific motivations for being single. influenced by the factor of wanting to resolve the crisis of trust in one's partner and the factor of one's own desires. Contribution: It is hoped that this research can increase understanding of future orientation in single adults and can apply it in life and can increase knowledge and insight in the field of psychology, especially with related topics.